PARP inhibition increases sensitivity to cisplatin in non-small-cell lung carcinoma via the induction of TET-dependent hydroxymethylation - Grdović, Nevena; Tolić, Anja; Jovanović, Mirna; Rajić, Jovana; Đorđević, Marija; Stojanović, Marijana; Hadžić, Stefan Marković; Marković, Tijana; Sarić, Ana; Dinić, Svetlana; Arambašić Jovanović, Jelena; Mihailović, Mirjana; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionPlatinum-based chemopotentiation by poly (ADP-ribose) polymerase (PARP) inhibitors (PARPi) has been confirmed in some non-small-cell lung carcinoma (NSCLC) models, but the molecular mechanisms of PARPi synergy with chemotherapeutics remain poorly clarified. This study aimed to evaluate the efficacy of PARPi niraparib in mitigating resistance to cisplatin through increased ten-eleven translocation (TET) enzymatic activity and 5-hydroxymethylcytosine (5hmC) level in human NSCLC model.MethodsThe chemosensitivity of human NSCLC, sensitive and multidrug-resistant (NCI-H460 and NCI-H460/R, respectively), lung adenocarcinoma cell line (A549), and normal embryonic lung fibroblasts (MRC-5) to increasing concentrations of cisplatin was studied by the MTT assay. The MTT and the median effect analyses were used to evaluate the efficacy of niraparib combinatorial synergy with cisplatin, dimethyloxalylglycine (DMOG), and vitamin C. The inhibition of PARP activity was determined by the PARP activity assay. The global level of 5hmC was examined by confocal microscopy, slot-blot, and flow cytometry, which was used for monitoring cell death at different stages. The protein level of lamin B, PARP1, procaspase-3, and TETs was assessed by Western blotting. The expression of the TET enzyme was analyzed by real-time quantitative PCR.ResultsThe chemosensitivity to cisplatin was found to be correlated with the level of 5hmC in NSCLC and MRC-5 cell lines. A549 was characterized with the lowest sensitivity to cisplatin and the 5hmC level and was selected for chemosensitization via PARPi-dependent restoration of the 5hmC level. Treatment of A549 cells with niraparib resulted in decreased PARP activity, increased 5hmC level, and synergism with cisplatin by promoting cisplatin-induced apoptosis. The treatment with niraparib and cisplatin resulted in synergistic effect in the hydroxylase activity of TET2 in terms of increased 5hmC production in A549 cells.ConclusionThe improved response to cisplatin following PARPi-mediated sensitization of A549 cells, accompanied by the restoration of 5hmC levels, provides additional insights into the epigenetic mechanisms underlying the synergy between PARPi and cisplatin. The use of PARPi in clinical settings could increase the number of patients enriched in 5hmC, who might benefit from platinum-based therapy. Additionally, targeting epigenetic marks could provide a molecular basis for personalized cancer therapy directed to overcome tumor resistance.